Combining Rice Straw Biochar With Leguminous Cover Crop as Green Manure and Mineral Fertilizer Enhances Soil Microbial Biomass and Rice Yield in South China - Xie, Zhijian; Shah, Farooq; Zhou, Chunhuo (Frontiers in Plant Science, 2022)
Whether combining rice-straw biochar (RSB) with leguminous cover crop (LCC) has synergistic effects in the rice production system or not, is still unknown. Two pot experiments were conducted to systematically explore the impacts of RSB on mass decomposition and nitrogen (N) release from LCC residues after incorporation into acidic paddy soil. Similarly, the effect of combining these two factors on soil nutrient status and microbial biomasses in the rice production system was also examined. Five treatments, namely, no N fertilizer (CK), 100% N fertilizer (150 kg N ha–1 as N100), 80% N fertilizer plus RSB (N80B), LCC (N80M), and a combination of RSB with LCC (N80BM), were included. The results indicated that biomass decomposition and N release pattern followed a double exponential decay model such that the addition of RSB slightly stimulated the rates of both mass decomposition and N release during the initial rapid phase of decomposition. Thereafter, it notably slowed down the rates of both these parameters during the relatively slower stage of incorporating LCC residues to paddy soil during early rice season. Compared to 100% N, applying 80% N in conjunction with RSB and/or LCC residue increased grain yield and its components (i.e., effective panicles, 1,000-grain weight, and fully filled grains) that subsequently increased N accumulation and its physiological use efficiency (PUEN) of rice shoot. Moreover, under 20% N, applying RSB and/or LCC residue remarkably increased the soil organic matter and total N, and soil microbial populations and biomasses, while the contents of NH4+ and NO3– were decreased in RSB-amended paddy soil (N80B and N80BM), in comparison with N100. Thus, combining RSB with LCC residue is a novel and promising management intervention for reducing mineral fertilizer use, improving soil fertility and rice production, and consequently minimizing the overall production cost in south China.